Solving the crystallographic structure of the Cl2J construct and occupancy titration trials to quantitatively determine isomer ratio - Rummel, Brittany L., author; Ho, P. Shing, advisor; Curthoys, Norman, committee member; Bamburg, James, committee member; Kennan, Alan, committee member (Colorado State University. Libraries, 2011)
Halogen atoms are commonly found in biological organic compounds such as plastic polymers, flame retardants, coolant fluids, insecticides and herbicides. Halogens are known to mediate neurotransmitters in the brain and are required for the production of many hormones (i.e. thyroxine). Because halogen atoms are frequently incorporated in pharmaceuticals and antibiotics (i.e. clindamycin and chloramphenicol), it is important to characterize the interactions that those atoms participate in. Currently, there is little information known about halogen bonds and these interactions are not modeled accurately by molecular simulations. The long-term objective of Dr. Shing Ho's laboratory has been to characterize halogen bonds through structural and energetic determinations. As part of that larger goal, the studies in this thesis aim to address the structure-energy relationship of chlorinated halogen bonds or X-bonds. The experimental assay that allowed the study of halogen bonds is the 4-stranded DNA Holliday junction. Incorporating engineered halogen bonds into the structure results in halogen bonds competing energetically against hydrogen bonds for stabilization of the junction. The structure that was refined in order to analyze chlorinated halogen bonds is referred to as the Cl2J construct. The Cl2J construct is a crystallized Holliday junction crystal in which 2 chlorine atoms are incorporated into the structure as chlorinated uracil nucleotides, and thus, sets chlorine halogen bonding energies and hydrogen bonding energies in opposition. Occupancy titrations were conducted to quantify isomeric ratios of halogen bond versus hydrogen bond stabilized junctions (X- and H-isomers, respectively) within these crystals. The initial estimate of the isomer ratios of the Cl2J construct was 50/50 X-to-H-isomer from the initial electron density maps. The crystallographic model and subsequent occupancy titration trials actually indicate a higher ratio of approximately 3/1 X-to-H-isomer ratio, respectively. The occupancy titrations and crystallographic models of other constructs, F2J, Br2J and I2J, were analyzed in comparison to the Cl2J construct in order to define a protocol that accurately quantifies these isomeric ratios. Differential scanning calorimetry (DSC) studies are also presented to corroborate in solution any conclusions drawn from occupancy titrations in the crystals.
Keywords: bond; chlorine; energy; halogen; structure; x-ray crystallography